PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) PADA POLA JARAK TANAM YANG BERBEDA DALAM SISTEM TABELA - Magfiroh, Nur; Lapanjang, Iskandar M.; Made, Usman (AGROTEKBIS, 2017)
The study aimed to find plant spacing for better growth and yield of wetland rice crops under direct seeded planting system. The study was arranged in a Randomized Block design with two factors i.e. two different spatial plantings and three kinds of Jajar Legowo patterns. The plant spacing of 25 cm x 25 cm with Jajar Legowo pattern of 2:1 produced highest grain yield (8.21 ton ha-1) followed by the plant spacing of 20cm x 20cm with Jajar Legowo pattern of 3:1 (7.21 ton ha-1). Jajar Legowo pattern of 3:1 resulted in better plant height (74.80cm), similarly plant spacing of 25cm x 25 cm also had same plant height, more tiller number (30.69) and panicles per clump, longer panicle length and more grain number. Key Words: Jajar Legowo, Plant spacing, and Rice.